Pigmented lesion at skin graft site: Part 2 - Múnera Patiño, Marcos Stivel; Ruiz, Juan David (Revista de la Asociación Colombiana de Dermatología y Cirugía Dermatológica, 2023)
62-year-old woman who underwent resection of acral lentiginous melanoma with subsequent appearance of hyperpigmentation at the grafted site, was diagnosed with skin graft hyperpigmentation, a frequent but rarely studied complication, and which rarely presents with intense hyperpigmentation.